Análisis de bonos para la implementación de acciones negociables en la empresa Electrocel. - Saavedra Choez, Richard Nixon (My University, 2018)
From the beginning the exchange of goods or cash, or the barter that with the passage of time was changing and increasing; thus the financial mathematics were evolving with new forms and methods for their better understanding of the change of the capital in the term of different times; Long-term and capital investments are affected by the passing of time by interests, with which the financial media have a wide knowledge and provide formulas for how to calculate (capital, interest, time, NPV, IRR) allowing mathematical calculations to set the payments that will be made over time. The success that the organization wants to achieve depends on a good financial strategy; the interests that increase the value of the quotas annually, it is carried out by means of formulas established by the financial mathematics that serve to obtain predictions and interpretations with fundamentals which will help the decision making. The realization of this case is based on the investigation of the current interest rate for its application in the investments accompanied by the financial formulas thus obtaining with the different investments to observe which will be the best decision making for an investment.
Desde los inicios el intercambio de bienes o efectivo, ósea el trueque que con el pasar del tiempo fue cambiando y en aumento; así las matemáticas financieras fueron evolucionando con nuevas formas y métodos para sus mejor entendiendo del cambio del capital en el plazo de tiempos diferentes; las inversiones de largo plazo y de capital son afectados con el pasar del tiempo por los intereses con lo que los medios financiero tienen un amplio conocimiento y otorgan fórmulas de como calcular (capital, interés, tiempo, VAN, TIR) permitiendo los cálculos matemáticos para fijar los pagos que se realizaran con el pasar del tiempo. De una buena estrategia financiera dependerá el éxito que quiere alcanzar la organización; los intereses que aumentan el valor de las cuotas anualmente, se la realiza mediante fórmulas establecida por las matemáticas financieras que sirven para obtener pronósticos e interpretaciones con fundamentos lo cual ayudara a la toma de decisiones. La realización de este caso se basa en la investigación de la tasa interés vigente para su aplicación en las inversiones acompañadas de las formulas financiera así obteniendo con las diferentes inversiones observar cual será la mejor toma de decisión para una inversión.
Keywords: MATEMÁTICAS FINANCIERAS; INVERSIÓN; INTERÉS; CAPITAL